SnP nanocrystals as anode materials for Na-ion batteries. Issue 23 (30th May 2018) - Liu, Junfeng; Wang, Shutao; Kravchyk, Kostiantyn; Ibáñez, Maria; Krumeich, Frank; Widmer, Roland; Nasiou, Déspina; Meyns, Michaela; Llorca, Jordi; Arbiol, Jordi; Kovalenko, Maksym V.; Cabot, Andreu
Abstract : Sodium ion batteries based on SnP NCs and sodium(i ) bis(fluorosulfonyl)imide electrolyte displayed high reversible capacities and cycling stability. Abstract : Tin monophosphide is a layered material consisting of Sn–P–P–Sn sandwiches that are stacked on top of each other to form a three dimensional crystallographic structure. Its composition and crystal structure makes it an excellent candidate anode material for sodium-ion batteries (SIBs). However, SnP is yet to be explored for such and other applications due to its challenging synthesis. In the present work, we report the synthesis of SnP nanocrystals (NCs) from the reaction of hexamethylphosphorous triamide (HMPT) and a tin phosphonate prepared from tin oxalate and a long chain phosphonic acid. SnP NCs obtained from this reaction displayed a spherical geometry and a trigonal crystallographic phase with a superstructure attributed to ordered diphosphorus pairs. Such NCs were mixed with carbon black and used as anode materials in SIBs. SIBs based on SnP NCs and sodium(i ) bis(fluorosulfonyl)imide (NaFSI) electrolyte displayed a high reversible capacity of 600 mA h g −1 at a current density of 100 mA g −1 and cycling stability for over 200 cycles. Their excellent cycling performance is associated with both the small size of the crystal domains and the particular composition and phase of SnP which prevent mechanical disintegration and major phase separation during sodiation and desodiation cycles. These results demonstrate SnP to be an attractive anode material for sodium ion batteries.